2015
DOI: 10.1371/journal.pone.0121794
|View full text |Cite
|
Sign up to set email alerts
|

Degree Correlations Optimize Neuronal Network Sensitivity to Sub-Threshold Stimuli

Abstract: Information processing in the brain crucially depends on the topology of the neuronal connections. We investigate how the topology influences the response of a population of leaky integrate-and-fire neurons to a stimulus. We devise a method to calculate firing rates from a self-consistent system of equations taking into account the degree distribution and degree correlations in the network. We show that assortative degree correlations strongly improve the sensitivity for weak stimuli and propose that such netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 58 publications
0
34
0
Order By: Relevance
“…The characteristic function of stable distribution can be classified using four parameters α, β, σ and µ, see [26,Definition 1.1.6], and the corresponding random variable is denote by S α (σ, β, µ). The parameter α is called the stability index and is the most important parameter for our purposes, since it relates to the exponent γ of the regularly-varying distribution.…”
Section: Stable Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic function of stable distribution can be classified using four parameters α, β, σ and µ, see [26,Definition 1.1.6], and the corresponding random variable is denote by S α (σ, β, µ). The parameter α is called the stability index and is the most important parameter for our purposes, since it relates to the exponent γ of the regularly-varying distribution.…”
Section: Stable Distributionsmentioning
confidence: 99%
“…For instance, it was shown that disassortative networks are easier to immunize and a disease takes longer to spread in assortative networks [11]. In the field of neuroscience, it was shown that assortative brain networks are better suited for signal processing [26], while assortative neural networks are more robust to random noise [12]. Under attacks, when edges or vertices are removed, assortative networks appear to be more resilient than disassortive networks [23,27].…”
mentioning
confidence: 99%
“…4). Work by Roxin [18], Schmeltzer et al [19], and unpublished work by Landau and Sompolinsky [33] has shown that the broadness and correlation of the joint degree distribution can lead to qualitative changes in the behavior of a spiking network. Further work is required to investigate whether and why these changes can be explained by the spectrum of the connectivity matrix derived here.…”
Section: Matrices With Heterogeneous Degree Distributionsmentioning
confidence: 99%
“…Note that by requiring that g is bounded and differentiable on the unit square outside of S 0 we allow the synaptic gain function to be a combination of discrete modulation (e.g., cell-type dependent connectivity for distinct cell types, as in [13]) and of continuous modulation (e.g., networks with heterogeneous and possibly correlated in- and out-degree distributions, as in [18, 19]).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of neuroscience degree-degree correlations are studied in the context of information spread in the brain. For instance, in [73], it is shown that assortative brain networks are better suited for signal processing, while assortative neural networks are shown to be more robust to random noise in [33].…”
Section: Influence On Network Properties and Processesmentioning
confidence: 99%